2010
DOI: 10.1002/erv.1047
|View full text |Cite
|
Sign up to set email alerts
|

Do abnormalities in regional cerebral blood flow in anorexia nervosa resolve after weight restoration?

Abstract: These data suggest that in the majority of cases rCBF does not return to normal following weight restoration. The implications for future research are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…This finding is in line with previous work that have shown unilateral left temporal hypoperfusion in 8 out of 15 and unilateral right temporal hypoperfusion in 5 out of 15 patients, which persisted at follow-up after restoration (Gordon, Lask, Bryant-Waugh, Christie, & Timimi, 1998). It is also in line with work such as that of Chowdhury et al (2003), Frampton et al (2011), andRastam et al (2001), but is contrary to work by Connan et al (2006) and Frank et al (2007).…”
Section: Memorysupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in line with previous work that have shown unilateral left temporal hypoperfusion in 8 out of 15 and unilateral right temporal hypoperfusion in 5 out of 15 patients, which persisted at follow-up after restoration (Gordon, Lask, Bryant-Waugh, Christie, & Timimi, 1998). It is also in line with work such as that of Chowdhury et al (2003), Frampton et al (2011), andRastam et al (2001), but is contrary to work by Connan et al (2006) and Frank et al (2007).…”
Section: Memorysupporting
confidence: 92%
“…Mainz, Schulte-Rü ther, Fink, Herpertz-Dahlmann, and Konrad (2012) found that grey-matter reductions at admission in patients with AN improved after weight recovery, with the strongest association found in the cerebellum. Frampton, Watkins, Gordon, and Lask (2011) found that regional cerebral blood flow levels did not return to normal in seven out of nine patients up to 4 years after diagnosis. Lateral and third ventricles enlargement has also been associated with starvation and malnutrition observed in AN.…”
Section: Brain Structurementioning
confidence: 83%
“…Six studies measured rCBF in subjects when they were underweight (Gordon et al, 1997; Naruo et al, 2001; Takano et al, 2001; Chowdhury et al, 2003; Key et al, 2006; Yonezawa et al, 2008). Six studies focused on pediatric patients (Gordon et al, 1997; Kuruoglu et al, 1998; Chowdhury et al, 2003; Lask et al, 2005; Komatsu et al, 2010; Frampton et al, 2011), and five on adult patients (Takano et al, 2001; Kojima et al, 2005; Key et al, 2006; Matsumoto et al, 2006; Frank et al, 2007; Yonezawa et al, 2008). Five studies compared rCBF before and after weight recovery, three with primarily pediatric subjects (Kuruoglu et al, 1998; Komatsu et al, 2010; Frampton et al, 2011), and two in adults (Kojima et al, 2005; Matsumoto et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Six studies focused on pediatric patients (Gordon et al, 1997; Kuruoglu et al, 1998; Chowdhury et al, 2003; Lask et al, 2005; Komatsu et al, 2010; Frampton et al, 2011), and five on adult patients (Takano et al, 2001; Kojima et al, 2005; Key et al, 2006; Matsumoto et al, 2006; Frank et al, 2007; Yonezawa et al, 2008). Five studies compared rCBF before and after weight recovery, three with primarily pediatric subjects (Kuruoglu et al, 1998; Komatsu et al, 2010; Frampton et al, 2011), and two in adults (Kojima et al, 2005; Matsumoto et al, 2006). There are four studies examining rCBF in currently-ill adult women, but the BMI for subjects in three of these studies (Naruo et al, 2001; Takano et al, 2001; Yonezawa et al, 2008) was substantially lower than in our study, leaving only one study of 11 subjects by Key et al (Key et al, 2006) containing subjects comparable to our AN-C group based on BMI and age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation